Accipitridae Vigors 1824 - Mather, Ellen K.; Lee, Michael S. Y.; Camens, Aaron B.; Worthy, Trevor H. (Zenodo, 2021)
Family Accipitridae Vigors, 1824 Subfamily indet. Gen. et sp. indet. Material NMV P.222435, distal left femur preserving intact distal end and 15.5 mm of shaft. Measurements (mm) Preserved length 26, DW 13.3, least SW 7.3, preserved condylus medialis depth 9.7, condylus medialis width 5.6, condylus lateralis depth 11.0, condylus lateralis width 6.1. Locality, stratigraphy and age 31° 11.237’S 140° 13.944 ʹ E Ericmas Quarry, Lake Namba, Frome Downs Station, South Australia, Namba Formation, Ericmas LF, late Oligocene. Collected by T. Flannery, 7/4/83. Remarks The specimen can be excluded from the Pandionidae and Cathartidae by the presence of a single muscular attachment on the planum popliteum, and from Falconidae and Sagittariidae by the linea intermuscularis caudalis remaining level and visible on the medial margin of the caudal face. The femur is consistent with accipitrids and has the following morphology. (Trait 1) The linea intermuscularis caudalis (Figure 12C: LIC) is highly distinct, running along the medial border of the caudal shaft face in a raised line, (2) but is not continuous with the tuberculum m. gastrocnemialis medialis, so there is no crista supracondylaris medialis. (3) The secondary origin point for the ligamentum collateralis lateralis is very faint and shallow, barely distinct from the surface of the bone. (4) The fovea tendineus m. tibialis cranialis is shallow. (5) The fossa poplitea (Figure 12B: FPop) is shallow, deepening slightly towards the distal end immediately proximal to the condyles. (6) The attachment scar on the planum popliteum (Figure 12B: PPAP) is positioned medially. (7) The impressio m. gastrocnemialis lateralis (Figure 12D: IG) is large and shallow. (8) The epicondylus lateralis (Figure 12A: EL) is short and very robust but has little projection from the condylus lateralis. The distal femur NMV P.222435 is from an accipitrid which exhibits the most similarity to those of species in Buteoninae, Aegypiinae, and most of Elaninae (see SI.2 for more detailed differential comparisons). It mainly differs from species in these subfamilies in lacking a prominent crista supracondylaris medialis, the position and shape of the attachment point on the planum popliteum, and the weak projection of the epicondylaris lateralis. As the distal femur is not a highly diagnostic section of the accipitrid skeleton, and the distal femur is not preserved in Archaehierax sylvestris specimen SAMA P.54998, NMV P.222435 is regarded as gen. et. sp. indet. The size difference between NMV P.222435 and the predicted size of the distal femur of SAMA P.54998 is greater than would be predicted from typical sexual dimorphism, which makes it unlikely the two are representatives of the same species (see comparative measurements below). Size comparisons of the three fossils The width measurements of the proximal humerus, distal humerus, distal tibiotarsus and distal femur of extant taxa were compared (see Appendix 1, Table S2) and showed that the distal width of the humerus was between 80% and 90% of the proximal width of the humerus, while the distal width of the tibiotarsus was between 75% and 110% the distal width of the femur in extant accipitrids. If the bones of Archaehierax sylvestris had similar ratios, then it can be predicted that the width of the missing distal humerus should fall in the range 23.4–26.4 mm, while that of the missing distal femur should be between 15.8 and 22.0 mm broad. Based on this, both the isolated distal femur NMV P222435 and the isolated distal humerus SAMA P.58917 are too small to belong to an individual the size of the A. sylvestris holotype. However, sexual dimorphism is known to be considerable and common in accipitrids (Brown and Amadon 1968; Marchant and Higgins 1993) and raises the possibility that these isolated fossils may belong to a smaller sex of the onespecies if they fall within a certain size range. Field et al. (2013) devised multiple algorithms for predicting body mass from skeletal measurements, while Campbell and Marcus (1992) predicted body mass based on the femur and tibiotarsus circumference. Using these, the mass of the bird for the Archaehierax sylvestris holotype is estimated as 3.7 kg based on the length of the coracoid facies articularis humeralis, 4.6 kg by the least shaft diameter/width of the tarsometatarsus, and 3.2 kg based on tibiotarsus least shaft circumference. The mass of the bird represented by the distal femur is calculated at 2 kg based on femur shaft width/diameter, or 1.6 kg based on shaft circumference. The mass of the bird represented by the distal humerus is calculated at 1.5 kg based on shaft width/diameter, or 1.6 kg based on circumference. Assuming these predictions are accurate, the femur represents a bird 46–67% smaller than the skeleton specimen, and the humerus one 60–67% smaller. This would be pushing accipitrid sexual dimorphism to its extreme limits, making it unlikely that the fossils represent a single species. However, these mass predictions use different elements, limiting their comparability. Nevertheless, while considering it likely that at least two accipitrids are represented, we consider it unwise to describe the smaller as a second species when size would be the only distinguishing factor and their congeneric status cannot be assessed. PCA analysis of limb measurements Length data for a range of post cranial measurements were visualised in PCA plotsto determine if there wasany correlation between them and preferred habitat. All PCAs used a variance-covariance matrix, iterative imputation for missing data (in the case of I.2 length of Gyps coprotheres ), and 1000 bootstrap replicates. See Appendix 2 for datasets, scree plots, biplots, PCA values. The first PCA used absolute length measurements of the carpometacarpus, ulna, tibiotarsus, tarsometatarsus, pedal digit 1 and pedal digit 2 (Figure 13A). In the resulting scatterplot PC1 (92.1% variance) was most strongly driven by the ulna, with some influence from the carpometacarpus (wings), the tarsometatarsus and tibiotarsus and PC2 (7% variance) by the tarsometatarsus and tibiotarsus (legs). Archaehierax sylvestris was positioned as a long-legged, short-winged taxon, well separated from other species. Both Spizaetus tyrannus and Spilornischeela grouped closely together, creating a cluster for forest-habitat accipitrids. Circus assimilis , which inhabits grassland and open woodland, was positioned intermediate between Archaehierax sylvestris and the forest taxa. A second PCA was run after log-transforming the measurements. In the resulting scatterplot (Figure 13B) PC1 (91.4% variance), was driven by almost all measurements, with those of the tibiotarsus and tarsometatarsus having slightly more influence than those of the wings and digits, and PC2 (3.3% variance) revealed that species were separated most strongly based on the tarsometatarsus length, with lesser influence from the digit lengths and tibiotarsus length. Archaehierax sylvestris grouped with the long-legged and short-winged taxa, but the distribution of the extant taxa changed. Spizaetus tyrannus and Spilornischeela were more widely separated, with the open-habitat taxon Circus assimilis positioned more closely to Spizaetus tyrannus . As size dominated the first two PCAs, a third PCA was performed with measurements standardised for size, by division of postcranial data by the height of the quadrate, an element which correlates strongly with skull size and therefore body size (Elzanowski et al. 2001). In the resulting scatterplot (Figure 13C), PC1 (67.2%) was most strongly driven by ulna length and to a lesser degree by carpometacarpus length, while PC2 (28.9%) was most strongly driven by tibiotarsus length and tarsometatarsus length. Archaehierax sylvestris occupied a more negative position on PC2 relative to Circus assimilis as the peak of the long-legged, shortwinged taxa, and Spizaetus and Spilornis clustered together closely once more. Archaehierax sylvestris fell intermediate between Circus assimilis and the forest accipitrid cluster. Phylogenetic analyses We performed phylogenetic analyses of morphological data only, and combined morphological and molecular data, using parsimony and Bayesian methods. We discuss all analyses below, but have most confidence in the analyses combining morphology and molecules, in particular the unlinked Bayesian analyses, for reasons discussed at the end. Analysis 1: Parsimony, morphology only, unordered characters The first analysis used only morphological data, with no ordering, constraints or weighting applied to the characters. The resulting 30 most parsimonious trees (hereafter MPTs) had a tree length of 1686 steps (SI.5 Figure 1). Coragyps atratus, Ciconia ciconia, Threskiornis spinicollis , and Sagittarius serpentarius were rooted as the outgroup (PP = 97%), while Pandion resolved as sister to Accipitridae with a support value of 97%. This is broadly concordant with independent molecular phylogenetic studies. Within Accipitridae, the tree is less congruent with DNA trees. The Accipitridae as a family had strong support (87%) with the non-Australian Perninae resolved as the most basal clade, which was strongly supported (87%) but had species left in a polytomy. The fossil Archaehierax sylvestris n. gen. et sp. resolved as a branch between the Circaetinae-Harpiinae-Aquilinae clade and all other subfamilies higher up the tree. However, support for this position was very weak (<50%). Analysis 2: Parsimony, morphology only, ordered characters Analysis 2 differed from Analysis 1 by ordering certain multistate characters which formed morphoclines (see SI.1). This generated four MPTs with a tree length of 1720. The resulting strict consensus tree (SI.5 Figure 2) is largely the same as for analysis 1, but with the following differences. The Accipitridae resolved with strong support slightly higher than the previous analysis (PP = 88%). The fossil Archaehierax sylvestris was resolved as being between the Elaninae and the Australian endemic Perninae on the phylogenetic tree, though support for this position was very weak (<50%). Analysis 3: Parsimony, morphology and DNA, ordered characters As the analyses based on morphology failed to resolve the taxa in a way that reflects strongly supported clades based on comprehensive molecular data, and the primary aim of the analysis was to assess how the fossil related to the well-corroborated clades of modern taxa, molecular data from six genes was added for 47 taxa (see Methods) forming a combined morphology and molecular data matrix used in Analysis 3. Parsimony analysis of this matrix produced three MPTs with a tree length of 1831 (See SI.5 Figure 3). Given the molecular data largely constrains the tree to the relationships dictated by molecular data alone, relationships were mostly the same as those in recent molecular studies (Nagy and Tökölyi 2014; Mindell et al. 2018). The position of the fossil Archaehierax sylvestris varied between the strict consensus tree and the bootstrap majority consensus tree of the same analysis. In the strict consensus tree (SI.5) the fossil resolved as nested within the Circaetinae, sister to Pithecophaga jefferyi . However, the bootstrap consensus tree resolved the fossil as its own branch between the Perninae-Gypaetinae and the Circaetinae-Aegypiinae clades with moderate (68%) support. Analysis 4: Bayesian inference, morphology + DNA, ordered The Bayesian analysis with molecular and morphological branch lengths unlinked produced a broadly similar tree for living taxa to the bootstrap consensus of the corresponding parsimony analysis, but with overall much stronger supports for higher-level clades (Figure 14). All subfamilies resolved as monophyletic, and the divergence nodes for all subfamilies and major clades were greater than 70% except for one. The fossil Archaehierax sylvestris resolved as a lineage between the Elaninae and the Perninae-Gypaetinae clades (i.e. non-elanine accipitrids). Support for Archaehierax plus a clade of all non-Elanine accipitrids was weak (44%), but there was moderate support (73%) for monophyly of all other non-elanine accipitrids excluding Archaehierax . When the branch lengths for the molecular and morphological data were linked (SI.5 Figure 4), the position of the fossil changed. Archaehierax sylvestris moved up the phylogeny and resolved as an independent branch above the Circaetinae-Aegypiinae clade but below the Harpiinae and relatives. Support for this node was stronger than that of the position resolved by the unlinked analysis, but still weak (56%). Summary All phylogenetic analyses resolved Archaehierax sylvestris with the Accipitridae, consistent with the conclusions drawn from the morphological descriptions, though its precise position within that family varied. Some analyses found it deeply nested within Accipitridae, closely related to, but outside buteonines, haliaeetines and accipitrines. These analyses include the morphology-only parsimony analyses, morphology+molecular parsimony and morphology+molecular Bayesian analysis with linked branch lengths. However, as discussed below, these deeply nested affinities for Archaehierax are problematic, and appear less plausible than the topology retrieved in the Bayesian analysis with branch lengths unlinked – where it was one of the most basal accipitrid lineages, with only Elaninae diverging before it (Figure 14). Amore precise and robust position for Archaehierax sylvestris is perhaps prohibited by missing data. Even with the 63 preserved elements, there is still a significant amount of missing data. The mandible and cranium, most of the sternum, the distal ends of the humeri, the pelvis, and most of the femora were not preserved. Thus, only 45% (135/300) of phylogenetic characters could be assessed in SAMA P.54998. : Published as part of Mather, Ellen K., Lee, Michael S. Y., Camens, Aaron B. & Worthy, Trevor H., 2021, An exceptional partial skeleton of a new basal raptor (Aves: Accipitridae) from the late Oligocene Namba formation, South Australia, pp. 1-33 in Historical Biology CLXVI on pages 24-28, DOI: 10.1080/08912963.2021.1966777, http://zenodo.org/record/5534487 : {"references": ["Vigors NA. 1824. Sketches in ornithology; or, observations on the leading affinities of some of the more extensive groups of birds. On the groups of Falconidae. Zoological Journal, 308 - 346", "Brown L, Amadon D. eds. 1968. Eagles, hawks and falcons of the world. Michelin House, London, England.", "Marchant S, Higgins PJ. 1993. Handbook of Australian, New Zealand and Antarctic Birds. Vol. 2: Raptors to Lapwings. Melbourne (Victoria): Oxford University Press.", "Field DJ, Lynner C, Brown C, Darroch SAF, Iwaniuk A. 2013. Skeletal correlates for body mass estimation in modern and fossil flying birds. PLoS One. 8 (11): e 82000. doi: 10.1371 / journal. pone. 0082000.", "Campbell KE, Marcus L. 1992. The relationship of hindlimb bone dimensions to body weight in birds. In: Papers in avian paleontology honoring Pierce Brodkorb. KE Campbell editor. Natural History Museum of Los Angeles County Science Series, 36, Los Angeles, California; p. 395 - 412", "Elzanowski A, Paul GS, Stidham TA. 2001. An avian quadrate from the Late Cretaceous Lance Formation of Wyoming. J Vert Paleo. 20 (4): 712 - 719. doi: 10.1671 / 0272 - 4634 (2000) 020 [0712: AAQFTL] 2.0. CO; 2.", "Nagy J, Tokolyi J. 2014. Phylogeny, historical biogeography and the evolution of migration in accipitrid birds of prey (Aves: Accipitriformes). Ornis Hungarica. 22: 15 - 35. doi: 10.2478 / orhu- 2014 - 0008.", "Mindell DP, Fuchs J, Johnson JA. 2018. Phylogeny, taxonomy and geographic diversity of diurnal raptors: Falconiformes, Accipitriformes and Cathartiformes. In: Sarasola JH, Grande J, Negro J, editors. Birds of Prey: biology and conservation in the XXI century. Springer, Cham, Switzerland; p. 3 - 32."]}